2003
DOI: 10.1191/1477153503li061oa
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patterns of use of occupant controlled office lighting

Abstract: This paper reports daily and seasonal patterns of lighting use in offices where occupants were able to vary the level of illuminance falling on their working areas. The results show that occupants set a wide range of illuminances, many of which are significantly below CIBSE Code recommendations leading to significant energy savings throughout the year. Although users report use of controls for a variety of reasons, the results of the long-term monitoring of switching behaviour reveals that very few in fact use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 9 publications
0
62
1
Order By: Relevance
“…When the cross-sectional questionnaire survey data could be complemented with additional datasets, such as environmental measurements, more sophisticated statistical methods could be used to find a connection between variables. This connection was described through correlation in many studies (Brundrett 1977) (Iwashita and Akasaka 1997) (Moore et al 2003) (Lutzenhiser 1992) (Price and Sherman 2006) (Guerra-Santin and Itard 2010) (Becker and Paciuk 2009) (Hua et al 2011). Others also managed to build a regression model to describe the nature of the connection (Frontczak et al 2012) (Humphreys 2005) (Raja et al 2001) (Meier and Rehdanz 2010) (Sardianou 2008) (Rijal 2008) (Bekö et al 2011) (Brager et al 2004) (Warren and Parkins 1984) (Rijal et al 2007).…”
Section: Data Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the cross-sectional questionnaire survey data could be complemented with additional datasets, such as environmental measurements, more sophisticated statistical methods could be used to find a connection between variables. This connection was described through correlation in many studies (Brundrett 1977) (Iwashita and Akasaka 1997) (Moore et al 2003) (Lutzenhiser 1992) (Price and Sherman 2006) (Guerra-Santin and Itard 2010) (Becker and Paciuk 2009) (Hua et al 2011). Others also managed to build a regression model to describe the nature of the connection (Frontczak et al 2012) (Humphreys 2005) (Raja et al 2001) (Meier and Rehdanz 2010) (Sardianou 2008) (Rijal 2008) (Bekö et al 2011) (Brager et al 2004) (Warren and Parkins 1984) (Rijal et al 2007).…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…These issues include: (1) participants knowingly or unknowingly misrepresenting their behaviour (also in Moore, et al (Moore et al 2003), Lutzenhiser (Lutzenhiser 1992) (Lutzenhiser 1993)), (2) participants may not recall their behaviour or their severity of discomfort (Burak Gunay et al 2014), and (3) participants may respond the way they think they are expected . These error types are categorized as measurement errors by Lohr (Leeuw et al 2008).…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, improvements in mood, lighting satisfaction, and discomfort achieved by giving people individual control of their lighting are proportional to the difference between the fixed illuminance and the preferred illuminance [37]. An extensive field study [38,39] has also shown that direct/indirect lighting suspended over each workstation and providing individual control is considered better than uniform lighting with simple switching, and it saves energy.…”
Section: Lighting Controls and Lenimentioning
confidence: 99%
“…Different people prefer varying illuminances for the same task. It has also been established that those buildings with most overrides are also the most energy efficient [34][35][36][37][38][39].…”
Section: Lighting Controls and Lenimentioning
confidence: 99%